The videogame industry does not exist : why we should think beyond commercial game production - Keogh, Brendan (MIT Press, 2023)
"Through a series of over 160 interviews, Keogh provides unprecedented access into the lives of game producers, exposing the limits of the concept of the "videogame industry" and challenging core assumptions in videogame research around creativity, professionalism, labor, diversity, education, and community" Provided by publisher